The economic impact of changes in local bank presence - Iftekhar Hasan; Krzysztof Jackowicz; Oskar Kowalewski; Łukasz Kozłowski (Regional Studies, 2019)
This study analyzes the economic consequences of changes in the local bank presence. Using a unique data set of banks, firms and counties in Poland over the period 2009–14, it is shown that changes strengthening the relationship banking model are associated with local labour market improvements and easier small and medium-sized enterprise access to bank debt. However, only the appearance of new, more aggressive owners of large commercial banks stimulates new firm creation.
Keywords: G21; G32; R11; 330; local economic activity; small and medium-sized enterprises (SMEs); entrepreneurship; local banks